2019
DOI: 10.1007/978-3-030-26172-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Reliability of Nanometer VLSI Systems

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The notations t ILD , k ILD are the thickness and the conductivity of Inter Layer Dielectric (ILD), which separates the metal wire and underlying layer. The temperature on the multi-segment interconnect tree is assumed to be a combination of the nonuniform distributed temperatures on each segment calculated by (5). For the node connecting to more than one segments, we suppose that there is negligible heat loss between the node and the underlying layer [35].…”
Section: B Space-time Related Temperature Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The notations t ILD , k ILD are the thickness and the conductivity of Inter Layer Dielectric (ILD), which separates the metal wire and underlying layer. The temperature on the multi-segment interconnect tree is assumed to be a combination of the nonuniform distributed temperatures on each segment calculated by (5). For the node connecting to more than one segments, we suppose that there is negligible heat loss between the node and the underlying layer [35].…”
Section: B Space-time Related Temperature Modelmentioning
confidence: 99%
“…For the node connecting to more than one segments, we suppose that there is negligible heat loss between the node and the underlying layer [35]. Based on (5), the temperature of the node over time can be expressed as:…”
Section: B Space-time Related Temperature Modelmentioning
confidence: 99%
“…where A HCI is a technology-dependent constant, f is the clock frequency, SW is the switching activity factor, t ox is the oxide thickness, V th is the threshold voltage and V GS is the gatesource voltage of the transistor, E 1 is a constant equal to 0.8 V/ nm [32] and t is the total time. The effect of HCI depends on the temperature of the device.…”
Section: Hot Carrier Injectionmentioning
confidence: 99%
“…Due to the interface traps in the gate oxide, the device characteristics such as threshold voltage and drain current are degraded. HCI [32] effect occurs in NMOS transistors. The effect of HCI in PMOS transistors is negligible.…”
Section: Hot Carrier Injectionmentioning
confidence: 99%
“…11 It is reported that the data center components outage can cost the providers between $8000 and $16,000 per minute. 12 According to the results of the report conducted by Ponemon Institute, the average cost of a data center outage has steadily increased from $505,502 in 2010 to $740,357 in 2016, indicating a 38% increase. 13 According to a report by Information Technology Intelligence Consulting in 2018, an hour of downtime on average costs data center operators $260,000, while a 5-min outage costs $2600.…”
mentioning
confidence: 99%